COMPASSION AND RELIGIOSITY: AN EMPIRICAL RESEARCH ON UNIVERSTY STUDENTS - Hızır HACIKELEŞOĞLU (Fırat University, 2019)
In this research, it is expressed as the basic problem whether there is a change in the level of compassion according to the religiousness tendency of the students of the university. The sense of compassion in terms of those who define himself as religious is important as a phenomenon frequently stuck on religion. Therefore, it is important to understand and explain the reflection of the emotion of compassion on the i